Native Wildflower Seed Production in Florida - Jeffrey G. Norcini (EDIS)
ENH-1035, a 20-page full-color brochure written by Jeffrey G. Norcini and designed by Florida Department of Agriculture and Consumer Services, provides information to growers interested in becoming wildflower seed producers. It describes the species, production practices, facilities and equipment needs and costs, seed testing and certification, memberships, markets and resources available. Published online by the UF Department of Environmental Horticulture, September 2006.